Analysis of Economic Activity of Foreign Direct Investors in Latvia - Jursa, Aleksejs (Vilnius University Open Series, 2022)
The aim of this article is to investigate the activity of foreign direct investors in Latvia and find out the main source of financing for foreign investors - new investments or reinvested earnings. To achieve the set goal, the methodology of the Sixth Edition of the International Monetary Fund's Balance of Payments and International Investment Position Manual was used to define the types of foreign direct investment (FDI). This methodology was adapted to Latvian data. At the request of the author, Lursoft IT Ltd selected business data on all registered companies with foreign capital in Latvia since 2005 and aggregate data were used in the analysis. Foreign direct investment in Latvia flows mainly in the form of reinvested earnings, due to the profit earned from operating activities in Latvia. While new investments or greenfield investments in equity is lower compared to the amount of reinvested earnings.